Tracking Student’s Order Thinking Process with AKT and Learning Path - Ahadia Busyaroh Asyhuri; Sajidan Sajidan; Baskoro Adi Prayitno (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2020)
This study is an exploratory qualitative, aimed to describe student’s order thinking process in remembering, understanding, and applying cognitive level based on Anderson Krathwohl Taxonomy (AKT) with learning path. There are 2 dimensions of AKT that cannot be separated and are equally important to maximize the potential of students and teachers in the learning process as well as learning outcomes. AKT differentiates the dimensions of the cognitive process into 2 levels of thinking, are low order thinking for the C1-C3 categories and high order thinking starting from C4-C6. The student must be mastered first on low-level thinking before reached a higher level. The development of a student’s order thinking process can be tracked with a learning path. A learning path is a route that students take to reach the learning goals. The selection of learning paths can be used as an alternative to developing student’s thinking process and scaffolding. Teachers are free to determine the route they feel more efficient to build students' high-order thinking. The sample of this research was selected by purposive random sampling consisted of 3 students in each level of high, middle, and low academic ability (HAA, MAA, and LAA). The research procedure sets up with knowing student's abilities, preparing instruments, conducting research, and analyzing the data. Results are: 1) The students' thinking process could be accessed using AKT and learning path; 2) The thinking process of students is influenced by academic ability in terms of the learning path; 3) All research subjects have not been able to reach the highest thinking process tested, namely PC3 so that a deeper analysis is needed to determine the cause; and 4) Learning path can be used as a tool to track students' unattainable thinking processes and scaffolding the “missed” thinking process as a solution